Neutrophil extracellular traps in tumor metabolism and microenvironment - Zhanrui Liu; Yuanyao Dou; Conghua Lu; Rui Han; Yong He (Biomarker Research)
Abstract Neutrophil extracellular traps (NETs) are intricate, web-like formations composed of DNA, histones, and antimicrobial proteins, released by neutrophils. These structures participate in a wide array of physiological and pathological activities, including immune rheumatic diseases and damage to target organs. Recently, the connection between NETs and cancer has garnered significant attention. Within the tumor microenvironment and metabolism, NETs exhibit multifaceted roles, such as promoting the proliferation and migration of tumor cells, influencing redox balance, triggering angiogenesis, and driving metabolic reprogramming. This review offers a comprehensive analysis of the link between NETs and tumor metabolism, emphasizing areas that remain underexplored. These include the interaction of NETs with tumor mitochondria, their effect on redox states within tumors, their involvement in metabolic reprogramming, and their contribution to angiogenesis in tumors. Such insights lay a theoretical foundation for a deeper understanding of the role of NETs in cancer development. Moreover, the review also delves into potential therapeutic strategies that target NETs and suggests future research directions, offering new perspectives on the treatment of cancer and other related diseases.